The Influence of the Contextual Teaching and Learning Model Assisted by Learning Videos in Improving Student Learning Outcomes and Motivation at SDN Sibangkua South Tapanuli - Siregar, Lenni Marlina; Hasratuddin, Hasratuddin; Anam, Rifat Shafwatul; Syahril, Syahril (Continuous Education: Journal of Science and Research, 2025)
The research aims to describe the difference in influence between the CTL learning model assisted by learning videos and ordinary learning on students' mathematics learning outcomes, describe the difference in influence between the CTL learning model assisted by video learning and ordinary learning on students' learning motivation, describe the interaction between learning and students' initial abilities on results students' mathematics learning, and describing the interaction between learning and students' initial abilities on students' learning motivation at SDN 100106 Sibangkua, South Tapanuli Regency. The research method used is a quasi-experimental method because students' conditions cannot be controlled. The data analysis technique uses 2x3 factorial Anova. The population of this study were students at SD Negeri 100106 Sibangkua, South Tapanuli Regency for the 2021/2022 academic year. The sample consisted of 2 classes consisting of 1 experimental class and 1 control class. The experimental class with the CTL model was assisted by video learning and the control class was taught using regular learning. The results of the research concluded that there was a difference in students' mathematics learning outcomes using the video-based CTL learning model with an average of 78.83 compared to regular learning with an average of 67.67. There is a difference in students' learning motivation using the video-based CTL learning model with a score of 70.42 and regular learning with a score of 66.07. There is an interaction between the learning model and initial mathematics abilities on students' mathematics learning outcomes (0.006<0.06). There is an interaction between the learning model and initial mathematics abilities on students' learning motivation (0.001<0.05).